A Study Of Early Neonatal Morbidity - Singh Kamaljit; Sekhon A.S; Singh Jagjit (Wolters Kluwer Medknow Publications, 1997)
Research question: What is the pattern of early neonatal morbidity in hospital born babies? Objectives: i) To study the pattern of early neonatal morbidity. ii) To identify the contributory factors. Study design: Cross- sectional. Settings: Rajendra Hospital attached to Government Medical College, Patiala. Participants: New â€" borns and their mothers. Study Variables: Prenatal care, maternal diseases during pregnancy, maternal haemoglobin level, maternal nutrition. Outcome variables: Morbidity rates. Low birth weight, Birth asphyxia, Neonatal infections, Birth trauma and Respiratory Distress Syndrome (RDS) . Statistical analysis: Proportions and X2 â€" test. Results: The study revealed that low birth weight (20%) and birth asphyxia (20%) were the common morbidity conditions followed by neonatal infections, birth trauma and respiratory distress syndrome. Early neonatal morbidity was less in babies of mothers who had received adequate prenatal care. Among the maternal diseases, antepartum haemorrhage and anemia contributed for low birth weight and birth asphyxia, Morbidity was comparatively more among babies of undernourished mothers.